Prosody adaptation in text-to-speech synthesis - Poh, Teng Chuan (2011)
A prosody adaptation text-to-speech system based on concatenation of spoken English words is presented in this paper. To make the resulting sentences sound natural, modifications are made to the prosody of the speech units using the Time-Domain-Pitch-Synchronous- Overlap-Add method. A prosody generator is built to generate the intonation pattern for the synthesised speech. An approach of smoothing the distortion at the boundaries of the concatenated units is proposed.